The Constitutional Structure of Local Government and Its Finances in Ukrain in Front of the Court of History - Havrylyuk, Ruslana (poltext, 2020)
Based on the anthroposociocuitural approach, the article explores the historical background for the emergence of the constitutional structure of local self-government and its finances in U kraine, the legal matrix of these phenomena in the Constitution of Ukraine. The conclusion is substantiated that the legal structure of the local government finances of the Tax Code of Ukraine contradicts the Constitution of Ukraine. The authors substantiate the need for innovative transformation of the constitutional structure of locai self-government of Ukraine within the framework of the. European Charter of Local Self-Government.
Keywords: local government; local government finance; Constitution of Ukraine; European Charter of Local Government